2015
DOI: 10.1155/2015/169194
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Intramuscular Injection of Levothyroxine following Myxoedema: A Practical Solution to an Old Crisis

Abstract: An 82-year-old female with known hypothyroidism was admitted to hospital after being found on the floor. On examination, she was unkempt, confused, bradycardic, hypothermic, and barely arousable. Initial biochemistry revealed a thyroid stimulating hormone (TSH) of >100 mU/L and free thyroxine (FT4) level of 1.5 pmol/L which supported a diagnosis of myxoedema coma. She was resuscitated and commenced on liothyronine, levothyroxine, and hydrocortisone and some improvement was made. It became apparent that she was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Despite advanced laboratory techniques and increased awareness of the disease, there are still cases of excessive dysfunction. (14,15). Hypo -and hyperthyroidism are usually caused by pathological processes in the thyroid gland, but may be caused by hypothalamus or pituitary (central hypothyroidism) or functional thyroid disorders in certain situations (16).…”
Section: Discussionmentioning
confidence: 99%
“…Despite advanced laboratory techniques and increased awareness of the disease, there are still cases of excessive dysfunction. (14,15). Hypo -and hyperthyroidism are usually caused by pathological processes in the thyroid gland, but may be caused by hypothalamus or pituitary (central hypothyroidism) or functional thyroid disorders in certain situations (16).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid dysfunction is common, readily identifiable and easily treatable but if undiagnosed or untreated can have profound adverse consequences 2,3 . Despite an increase in thyroid disease awareness and the availability of sensitive laboratory assays for the measurement of thyroid hormones it is remarkable that instances of extreme thyroid dysfunction continue to occur 4,5 . Hypothyroidism and hyperthyroidism most commonly arise from pathology within the thyroid gland (primary thyroid disease), although rarely they may arise from disorders of the hypothalamus or pituitary (central) or from peripheral causes 6 .…”
Section: Introductionmentioning
confidence: 99%
“…There are records of parenteral levothyroxine use as early as 1984,3 however just a handful of case studies since. Studies have demonstrated the successful use of intramuscular levothyroxine therapy in patients with both non-adherence4 and malabsorption 5. That being said, there are no well-established guidelines on its use6 and just five adult cases have been examined in the literature.…”
Section: Discussionmentioning
confidence: 99%